'Why don't you try it again?' A comparison of parent led, home based interventions aimed at increasing children's consumption of a disliked vegetable. (1st April 2015) - Holley, Clare E.; Haycraft, Emma; Farrow, Claire
Highlights: A home based intervention was developed to increase child vegetable intake. Intervention elements of repeated exposure, modelling and rewards were compared. A rewards and repeated exposure intervention was successful at increasing intake. A repeated exposure, modelling and rewards intervention was also successful. Parent led interventions can successfully be used to increase vegetable intake. Abstract: Previous research suggests that the use of modelling and non-food rewards may be effective at increasing tasting, and consequential liking and acceptance, of a previously disliked food. Although successful school-based interventions have been developed, there is a lack of research into home-based interventions using these methods. This study aimed to develop and investigate the efficacy of a parent led home-based intervention for increasing children's acceptance of a disliked vegetable. A total of 115 children aged 2–4 years were allocated to one of four intervention groups or to a no-treatment control. The four intervention conditions were: repeated exposure; modelling and repeated exposure; rewards and repeated exposure; or modelling, rewards and repeated exposure. Children in all of the intervention conditions were exposed by a parent to daily offerings of a disliked vegetable for 14 days. Liking and consumption of the vegetable were measured pre and post-intervention. Significant increases in post-intervention consumption were seen in the modelling, rewards and repeated exposure condition and the rewards and repeated exposure condition, compared to the control group. Significant post-intervention differences in liking were also found between the experimental groups. Liking was highest (>60%) in the modelling, rewards and repeated exposure group and the rewards and repeated exposure group, intermediate (>26%) in the modelling and repeated exposure and repeated exposure groups, and lowest in the control group (10%). Parent led interventions based around modelling and offering incentives may present cost efficient ways to increase children's vegetable consumption.